OUTBREAK OF TOBAMOVIRUSES AND POTEXVIRUSES ASSOCIATED WITH DISEASE EPIDEMICS IN TOMATO PRODUCTION AREA OF IRAQ - Hasaneen K. Obaid; Mustafa Adhab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was initiated to examine the tomato-infecting viruses belonging to the Tobamovirus and Potexvirus genera in Iraq. Field observations and surveys were carried out for three successive cropping seasons (2020/21 to 2022/23) in selected tomato production areas. The purpose was to identify the main viruses associated with tomato epidemics and assess the impact of different tomato cultivars on disease occurrence. A total of 700 tomato leaf samples were collected from seven governorates (Baghdad, Diyala, Babylon, Najaf, Kerbala, Nasiriya, and Basrah) and tested using pathogen-specific immunostrip kits. The survey showed a presence of Tomato brown rugose fruit virus (ToBRFV), Tobacco mosaic virus (TMV), Pepper mild mottle virus (PMMoV), Cymbidium mosaic virus (CymMV), Odontoglossum ringspot virus (ORSV), Cucumber green mottle mosaic virus (CGMMV), Pepino mosaic virus (PepMV) and Potato virus X (PVX) in tomato fields in Iraq. ToBRFV secured the highest relative incidence in tomato fields (7 governorates) followed by PepMV and CymMV and PMMoV (6 out of 7 governorates) and CGMMV, TMV (5 governorates), and PVX (3 governorates). The least was ORSV (only in Basrah). To our knowledge, this is the first comprehensive survey investigating Tobamovirus and Potexvirus on tomato fields in Iraq and the first report of ToBRFV, PMMoV, CymMV, ORSV, CGMMV and PepMV infecting tomato crops in Iraq.